(untitled) (Nepal Medical College Journal, 2025)
Menstruation is a natural biological process in females. It is often associated with stigmas and misconceptions, particularly among the males. Understanding male perception towards menstruation is crucial for promoting awareness and reducing gender-based biases. Despite its significance, men’s perceptions on menstruation are generally poorly understood, which can impact societal views and relationships. This study aimed to find the perception and knowledge of menstruation among male undergraduate students in Dhangadhi Sub-metropolitan City, Nepal. The rationale was to address the gap in understanding male perception, which significantly influence societal views on menstruation. A cross-sectional survey of 350 students was conducted using semi-structured questionnaire to assess socio-demographic characteristics, perceptions, knowledge, and experiences related to menstruation. The study revealed that 52.3% of students held negative perception, while 47.7% had positive views. A significant proportion (56.3%) lacked adequate knowledge about menstruation. Socio-demographic factors like ethnicity, family type, and educational level were significantly associated with the perception. The study highlights the need for awareness programs to improve menstrual health literacy and reduce stigma. Significance: The findings underscore the importance of involving the males in menstrual health awareness to combat societal stigma and promote men’s involvement in women’s sexual and reproductive health.